2000
DOI: 10.1159/000054520
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Estradiol Pretreatment on the Response to <i>d</i>-Amphetamine in Women

Abstract: Little is known about the interactions between ovarian hormones and responses to psychoactive drugs in humans. Preclinical studies suggest that ovarian hormones such as estrogen and progesterone have direct and indirect central nervous system actions and that these hormones can influence behavioral responses to psychoactive drugs. In the present study, we assessed the subjective and physiological effects of d-amphetamine (AMPH; 10 mg p.o.) after pretreatment with estradiol. Two groups of healthy, regularly cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 23 publications
7
51
0
Order By: Relevance
“…Findings in the present study are consistent with clinical studies in which estradiol was administered to follicular phase women before exposure to d-amphetamine (Justice and de Wit, 2000b). Estradiol levels, 10 times the usual follicular phase levels, did not significantly enhance most positive subjective responses to d-amphetamine (Justice and de Wit, 2000b). Women studied at the early follicular phase of the menstrual cycle, when estradiol levels are low, and at the late follicular phase, when estradiol levels are high, also did not respond differently to d-amphetamine (Justice and de Wit, 2000a).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Findings in the present study are consistent with clinical studies in which estradiol was administered to follicular phase women before exposure to d-amphetamine (Justice and de Wit, 2000b). Estradiol levels, 10 times the usual follicular phase levels, did not significantly enhance most positive subjective responses to d-amphetamine (Justice and de Wit, 2000b). Women studied at the early follicular phase of the menstrual cycle, when estradiol levels are low, and at the late follicular phase, when estradiol levels are high, also did not respond differently to d-amphetamine (Justice and de Wit, 2000a).…”
Section: Discussionsupporting
confidence: 90%
“…The highest dose of estradiol studied did not alter the cocaine dose-effect curve appreciably from control conditions. Findings in the present study are consistent with clinical studies in which estradiol was administered to follicular phase women before exposure to d-amphetamine (Justice and de Wit, 2000b). Estradiol levels, 10 times the usual follicular phase levels, did not significantly enhance most positive subjective responses to d-amphetamine (Justice and de Wit, 2000b).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Justice and de Wit (2000a) found that estradiol given to women during the early follicular phase increases some, but not all, positive subject-rated effects of amphetamine. Others have administered progesterone during the follicular phase, when endogenous levels are negligible, and found that it decreases physiological and positive subject-rated effects of cocaine in women (Evans and Foltin, 2006a;Sofuoglu et al, 2004).…”
Section: Introductionmentioning
confidence: 94%